A functioning black adenoma of the adrenal cortex: A clinico-pathological entity - Visser, J. W. (1974)
A 25-year-old woman is described who had suspected hyperfunction of the adrenal cortex. She complained of fatiguability, excessive hair growth, and attacks of swelling of the face, hands, and ankles. Moreover she had a `moon face', hypertension, a `buffalo hump', and livid striae of the loins and hypogastrium. Adrenal function tests yielded values which could not be clearly interpreted. Operation showed a `black adenoma' of the adrenal cortex on the right side. As far as it is known this is the first published case of this extremely rare lesion which was operated upon and caused nearly complete remission of the endocrine disturbance.